Novel wobble-defended M-MULTOPS structure and its application in detecting network abnormal traffic - SUN Zhi-xin1; TANG Yi-wei1; GONG Jing1 (Tongxin xuebao)
A new detection method: wobble defended M-MULTOPS（modified-multi-level tree for online packet statistics） structure was presented.Aiming at the change of network traffic in core routers,ABF（adapted bloom filter） algorithm to assemble destination addresses to the IP packets was employed.And it put forward M-MULPOTS struc-ture to analyze results of the ABF algorithm,monitoring changes of network traffic and detecting network flow ab-normity in real time.For making use of the Wobble-defended M-MULTOPS structure,the method can work steadily and exactly,even when the traffic of network is wobbling terribly by the pulse attack.And because the M-MULTOPS inherits the MULTOPS ’s flexible attribution,it declined the spending of system resources at maximum.A detection system em-ploying this method has been run successfully in routers as an individual module.